Inner Conflict of Character in Nine Perfect Strangers Novel by Liane Moriarty - Palungan, Samuel Jacob Abednego; Moelier , Dahlia D.; Asyrafunnisa, Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2024)
This research aims to find and analyse the types of inner conflicts and types of ego defence mechanisms specifically in the novel. The primary data source used in this research comes from the novel Nine Perfect Strangers written by Liane Moriarty. In analysing the data, the author used descriptive qualitative research method through psychological approach. Data is obtained by using reading, recording, and analysing techniques. While in classifying the data, the author uses the theory of Psychoanalysis by Sigmund Freud. The writer found that the novel Nine Perfect Strangers written by Liane Moriarty contains 24 data divided into 8 inner conflicts consisting of 3 Id, 2 Ego, and 3 Superego data. While the data that includes Ego Defence Mechanism there are 16 data which are divided into 3 Displacement, 1 Projection, 2 Regression, 4 Sublimation, 2 Rationalization, and 4 Fantasy and Stereotype, . From the data above, it can be said that Id, Superego, Sublimation, and Fantasy and Stereotype data are the dominant data